The Mineral Wool Industry in Indiana - W. N. Logan (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1932)
WHAT is mineral wool? This question is frequently asked by those unacquainted with its manufacture. The word "mineral" suggests that it is of mineral origin; the word "wool" suggests that it is of animal origin; but the only similarities it has to wool are its fibrous character and its white fleecyness. Mineral wool is a fiber produced by melting rock to a glasslike condition and blowing the glass into fine white, wool-like threads. A -number of the products fabricated from-mineral wool are used for some form of insulation, but mineral wool is adaptable to many other uses. It is used in the manufacture-of pipe covering designed to with; stand the high temperatures produced in steam pipes. In a similar form of insulation it is used to cover boilers and furnaces. It is used in ,the fabrication of upholstery tow for sofas and car seats: In acoustics it has many uses, such as acoustifibroblock, which is used in floors to destroy sound and vibration, and acoustic mat, which is used under carpets to destroy sound. In the insulation of houses, loose wool and granulated wool are used beneath attic floors and between the studding in frame buildings to prevent the escape of heat in winter and the entrance of heat in summer. Mineral wool is used also in fabrication of linofelt, which is a quilted form of insulation; in fibrofelt, which is an insulating board; in the fabrication of lith, which is an insulating block; in anti-fibroblock ,which is used in insulation and refrigeration; in flexfelt; in loose wool; in pressed block; in heavy oiled wool; in dark oiled block; and for many other purposes. The materials used in the manufacture of mineral wool are of two kinds. The first is a rock which contains silt, clay and silica, with smaller amounts of lime and magnesia. The second is a more highly calcareous rock which may carry a small amount of magnesia. The latter is used as flux to assist in the melting of the former. The relative proportion of the alumina-iron-silica content to the lime-magnesia content is normally as fifty to fifty but a considerable range is possible.